Impact of transforming mental health services for young people in England on patient access, resource use and health: a quasi-experimental study - Stephen Rocks; Mina Fazel; Apostolos Tsiachristas (BMJ Open)
Objective To evaluate the impact of child and adolescent mental health services (CAMHS) transformation in South East England on patient access, resource utilisation and health outcomes.Design In an observational study, we use difference-in-differences analysis with propensity score matching to analyse routinely collected patient level data.Setting Three CAMHS services in South East England.Participants All patients attending CAMHS between April 2012 and December 2018, with more than 57 000 spells of care included.Main outcome measures The rate and volume of people accessing CAMHS; waiting times to the first contact and waiting times between the first and second contact; and health outcomes, including the Strengths and Difficulties Questionnaire (SDQ) and the Revised Child Anxiety and Depression Scale (RCADS).Results The intervention led to 20% (incidence rate ratio: 1.20; 95% CI: 1.15 to 1.24) more new patients starting per month. There was mixed evidence on waiting times for the first contact. The intervention led to 10% (incidence rate ratio: 1.10; 95% CI: 1.02 to 1.18) higher waiting time for the second contact. The number of contacts per spell (OR: 1.08; 95% CI: 0.94 to 1.25) and the rereferral rate (OR: 1.06; 95% CI: 0.96 to 1.17) were not significantly different. During the post intervention period, patients in the intervention group scored on average 3.3 (95% CI: −5.0 to −1.6) points lower on the RCADS and 1.0 (95% CI: −1.8 to -0.3) points lower on the SDQ compared with the control group after adjusting for the baseline score.Conclusions Overall, there are signs that transformation can help CAMHS achieve the objectives of greater access and improved health outcomes, but trade-offs exist among different performance metrics, particularly between access and waiting times. Commissioners and providers should be conscious of any trade-offs when undertaking service redesign and transformation.